Trismus as a rare presenting symptom in a pediatric nasopharyngeal carcinoma - Maithrea, N.; Periyathamby, S.; Mohamad, Irfan (Elsevier, 2017)
Nasopharyngeal carcinoma (NPC) has a diverse incidence pattern but remains a rare tumour in the pediatric age group. Childhood nasopharyngeal carcinoma usually presents in the second decade of life. Paediatric NPC cases present a diagnostic challenge due to the high prevalence of common NPC presenting symptoms of nasal obstruction, serous otitis media and hearing problems among children. Furthermore, adenoid tissue is most often present, and a biopsy in an outpatient setup would be difficult. However, trismus on initial presentation is uncommon, and even in adults is a therapy related complication. As such, surgeons should have a high index of suspicion in NPC endemic areas, and a lower threshold for imaging in these cases as overall outcome appeared to be similar between adult and childhood NPC.